1990
DOI: 10.1007/bf00178991
|View full text |Cite
|
Sign up to set email alerts
|

The demonstration of choline acetyltransferase activity in cultured vestibular ganglion cells from the fetal rat

Abstract: Incubation of vestibular ganglion cells from the rat fetus was successfully done demonstrating bipolar and multipolar cells in the cell cultures produced. Further, the presence of choline-acetyltransferase-positive cells was confirmed immunohistochemically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Their peripheral processes receive and conduct stimuli from hair cells, and the central processes transmit this information to neurons located within nuclei of the brain stem (Gray Engstrom 1969, Curthoys 1981, gerbil (Perachio and Kevetter 1985), cat (Richter and Spoendlin 1981), rhesus monkey (Kitamura and Suzuki 1989). Recent studies have revealed the existence of the population of multipolar neurons within VG in the rat (Yamashita and Sekitani 1990), guinea pig (Ballantyne and Engstrom 1969), cat (Chat and Sans 1979) and humans Belal, Jr. 1981, Kitamura andKimura 1983). The literature in the field contains only a few papers dealing with the immunohistochemical features of VG neurons from chick and rat embryos cultured nerve cells Sekitani 1990, Yamashita et al 1991) in adult mouse (Inafuku et al 2000, Tritto et al 2009, guinea pig (Yamashita et al 1992), gerbil (Kevetter and Leonard 2002), chinchilla (Iurato et al 1974), pigeon (Li et al 2007) and in humans (Kanonier et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their peripheral processes receive and conduct stimuli from hair cells, and the central processes transmit this information to neurons located within nuclei of the brain stem (Gray Engstrom 1969, Curthoys 1981, gerbil (Perachio and Kevetter 1985), cat (Richter and Spoendlin 1981), rhesus monkey (Kitamura and Suzuki 1989). Recent studies have revealed the existence of the population of multipolar neurons within VG in the rat (Yamashita and Sekitani 1990), guinea pig (Ballantyne and Engstrom 1969), cat (Chat and Sans 1979) and humans Belal, Jr. 1981, Kitamura andKimura 1983). The literature in the field contains only a few papers dealing with the immunohistochemical features of VG neurons from chick and rat embryos cultured nerve cells Sekitani 1990, Yamashita et al 1991) in adult mouse (Inafuku et al 2000, Tritto et al 2009, guinea pig (Yamashita et al 1992), gerbil (Kevetter and Leonard 2002), chinchilla (Iurato et al 1974), pigeon (Li et al 2007) and in humans (Kanonier et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical studies have revealed the presence of the population of cholinergic neurons within VG in the rat (Yamashita and Sekitani 1990), chick embryo Sekitani 1990, Yamashita et al 1991) adult rat (Wicke et al 1976), squirrel monkey (Baurle et al 1999), chinchilla (Iurato et al 1974) and humans (Popper et al 2002a). The histochemical studies performed on rats (Wicke et al 1976) have revealed the three types of cholinergic neurons: weakly, medium and strongly stained.…”
Section: Introductionmentioning
confidence: 99%